Manajemen Bimbingan Konseling di SLB Paulus Tomohon - Meisie L. Mangantes (Peneliti.net, 2021)
Along with efforts to achieve educational goals at SLB Paulus Tomohon, the application of the role of Guidance in learning is very possible because it is expected to support the achievement of learning effectiveness and productivity. Regrettably, however, it seems that the implementation of the Guidance and Counseling role is still receiving less attention. In learning, teaching and providing skills training is a top priority, while the task of guiding is still often neglected, teachers have not realized the importance of the role of guidance as an optimal supporter of learning. Starting from this problem, the purpose of this study is to describe the efforts of counseling guidance in overcoming the problems of mentally retarded students in the classroom. The results showed that: The management of the guidance service program at SLB Paulus Tomohon has not been implemented properly starting from planning, program preparation, to evaluation. There has not been any visible effort to implement it, thus requiring the implementation of guidance services to be incidental. The implementation process is carried out with a situational and conditional approach, taking into account the problems or difficulties that appear in students.